ALECTINIB TREATMENT OF ALK POSITIVE NON SMALL CELL LUNG CANCER PATIENTS WITH BRAIN METASTASES: OUR CLINICAL EXPERIENCE - Simonida Crvenkova (Macedonian Academy of Sciences and Arts, 2020)
Summary: Anaplastic lymphoma kinase (ALK) rearrangement is identified in approximately 3-7% of all metastatic non-small cell lung cancer (NSCLC) patients, and ALK tyrosine kinase inhibitors (TKIs) have revolutionized the management of this subset of lung cancer cases. Purpose: This study aims to show alectinib (TKI) effectiveness and safety with focus on alectinib intracranial efficacy for ALK+ NSCLC patients. Case presentation: Patient 1 was a 46-year-old woman diagnosed with non-small cell lung cancer with an echinoderm microtubule-associated protein-like 4-anaplastic lymphoma kinase fusion gene (ALK+). She presented with intracranial and liver metastases and poor performance status of ECOG 3. Alectinib was initiated as a second line therapy, after whole brain irradiation and discontinuation of first line chemotherapy after two cycles, due to the central nervous system progression and liver metastases. Good response was consequently achieved, characterized with improved overall performance and without significant adverse events. Patient 2 was a 53-year old man with left sided lung adenocarcinoma surgically treated in 2017. Post-operative pTNM stage was IIB with a positive resection margin- R1. He received adjuvant chemotherapy and radiotherapy. In 2019, after two and half years of being disease free, he presented with severe cerebral symptoms leading to poor performance status. CT scan of the brain showed multiple brain metastases. He was treated with first line alectinib after completion of whole brain radiotherapy. In 5 months period he got significantly better and able for work again. Conclusions: We recommend alectinib as a first and second line treatment approach for ALK+ NSCLC patients, in particular the ones with brain metastases at the time of diagnosis and poor PS.
Keywords: brain metastasis; ALK+ NSCLC patients; alectinib